Comportamento governado por regras e responder relacional: uma análise experimental - Gomes, Cainã Teixeira (2018)
Since he was coined by Skinner (1963), the term "rule-governed behavior" has been the subject of debate on how it should be conveniently defined and studied experimentally. Throughout five experiments, the pertinence of the RFT (Relational Frame Theory) proposal was evaluated, which proposes that the critical operant for rule-following is the arbitrarily applicable relational responding. For this, a multiple-exemplar training was done in a matching-to-sample task with one of two contextual stimuli, whose purpose was to assign a contextual cue function to these two stimuli for the same and opposite relational response. Then, it was trained and tested derived rule-following, under the control of a rule composed of a novel stimulus, a contextual cue of same or opposite, and a conditional stimulus whose function was directly established. Finally, there was a phase in which the participants had to respond to these rules depending on the presence of one of the two stimuli, and in the presence of one, the rule was reinforced and in the presence of the other, any other response was reinforced. The objective of this last phase was to establish antecedent control of the follow-up derived from rules. In Experiment 1, it was shown that it is possible to train, and test derived rule-following with cues of same and opposite and that seven of eight participants were able to establish antecedent control of this operant. In Experiments 2 and 3, it was found that the training that established the contextual cues that facilitated derived rule-following and antecedent control was achieved through the relational training with the words "is equal to" and "is the opposite of" (relational training used in Experiment 3), in relation to the use of words without relational training and in relation to the use of meaningless syllables in the training (relational training used in Experiment 2). In Experiment 4, we tested the assumption that performance in the first three experiments had pre-experimentally established relationships of bigger-than/smaller-than comparison between members of two relational relay networks (composed of keyboard numbers). For this, in the training phase and rule-following test, the pressure responses of one of the eight keys were replaced by responses of selecting one of eight randomly arranged senseless images. Two phases were added in this experiment: non-arbitrary relational training of comparison (with the same structure as the training of equality and opposition), aimed at establishing the tips of bigger-than/smaller-than; and the arbitrary relational training, which aimed to establish two relational networks of comparison with four stimuli each. The results showed that the hypothesis was correct, since the performances of the participants in the experiment were functionally equivalent to those observed in the first experiments. To control the effects of pre-experimentally learned relations, Experiment 5 was designed to assess whether arbitrary relational training of same and opposite was critical to the performance observed in the four previous experiments. The results showed that it didn’t. It is concluded that the relational responding could be a relevant operant for learning what has traditionally been called rule-governed behavior